Surgical management of spine injuries in severe polytrauma patients: a retrospective study. (3rd July 2020) - Joubert, C.; Cungi, P.-J.; Esnault, P.; Sellier, A.; de Lesquen, H.; Avaro, J.-P.; Bordes, J.; Dagain, A.
Abstract: Background: Optimal surgical management of spinal injuries as part of life-threatening multiple traumas remains challenging. We provide insights into the surgical management of spinal injuries in polytrauma patients. Methods: All patients from our polytrauma care network who both met at least one positive Vittel criteria and an injury severity score (ISS) >15 at admission and who underwent surgery for a spinal injury were included retrospectively. Demographic data, clinical data demonstrating the severity of the trauma and imaging defining the spinal and extraspinal number and types of injuries were collected. Results: Between January 2012 and December 2016, 302 (22.2%) patients suffered from spinal injury (143 total injuries) and 83 (6.1%) met the inclusion criteria. Mean ISS was 36.2 (16–75). Only 48 (33.6%) injuries led to neurological impairment involving the thoracic ( n = 23, 16.1%) and lower cervical ( n = 15, 10.5%) spine. The most frequent association of injuries involved the thoracic spine ( n = 42). 106 spinal surgeries were performed. The 3-month mortality rate was 2.4%. Conclusions: We present data collected on admission and in the early postoperative period referring to injury severity, the priority of injuries, and development of multi-organ failure. We revealed trends to guide the surgical support of spinal lesions in polytrauma patients.